Effect of oxidizing and reducing atmospheres on Ba(Ti0.90 Zr0.10)O3:2V ceramics as characterized by piezoresponse force microscopy - Moura, Francisco; Simões, Alexandre Zirpoli [UNESP]; Riccardi, Carla dos Santos [UNESP]; Zaghete, Maria Aparecida [UNESP]; Varela, José Arana [UNESP]; Silva, Elson Longo da [UNESP] (My University, 2011)
The effect of annealing atmospheres (Atamb, N2 and O2) on the electrical properties of Ba(Ti0.90Zr0.10 )O3:2V (BZT10:2V) ceramics obtained by the mixed oxide method was investigated. X-ray photoelectron spectroscopy (XPS) analysis indicates that oxygen vacancies present near Zr and Ti ions reduce ferroelectric properties, especially in samples treated in an ambient atmosphere (Atamb ). BZT10:2V ceramics sintered in a nitrogen atmosphere showed better dielectric behaviour at room temperature with a dielectric permittivity measured at a frequency of 10 kHz equal to 16800 with dielectric loss of 0.023. Piezoelectric force microscopy (PFM) images reveal improvement in the piezoelectric coefficient by sintering the sample under nitrogen atmosphere. Thus, BZT10:2V ceramics sintered under a nitrogen atmosphere can be useful for practical applications which include nonvolatile digital memories, spintronics and data-storage media.
Keywords: Ferroelectrics; Powder metallurgy; X-ray diffraction; Dielectric response